Neural substrates for allocentric‐to‐egocentric conversion of remembered reach targets in humans. (22nd March 2018) - Chen, Ying; Monaco, Simona; Crawford, J. Douglas
Abstract: Targets for goal‐directed action can be encoded in allocentric coordinates (relative to another visual landmark), but it is not known how these are converted into egocentric commands for action. Here, we investigated this using a slow event‐related fMRI paradigm, based on our previous behavioural finding that the allocentric‐to‐egocentric (Allo–Ego) conversion for reach is performed at the first possible opportunity. Participants were asked to remember (and eventually reach towards) the location of a briefly presented target relative to another visual landmark. After a first memory delay, participants were forewarned by a verbal instruction if the landmark would reappear at the same location (potentially allowing them to plan a reach following the auditory cue before the second delay), or at a different location where they had to wait for the final landmark to be presented before response, and then reach towards the remembered target location. As predicted, participants showed landmark‐centred directional selectivity in occipital–temporal cortex during the first memory delay, and only developed egocentric directional selectivity in occipital–parietal cortex during the second delay for the 'Same cue' task, and during response for the 'Different cue' task. We then compared cortical activation between these two tasks at the times when the Allo–Ego conversion occurred, and found common activation in right precuneus, right presupplementary area and bilateral dorsal premotor cortex. These results confirm that the brain converts allocentric codes to egocentric plans at the first possible opportunity, and identify the four most likely candidate sites specific to the Allo–Ego transformation for reaches. Abstract : Using an event‐related, cue separation fMRI design, we investigated brain areas involved in the conversion of target representation in allocentric coordinates (relative to an external visual landmark) into egocentric reach commands (relative to the body). We identified one posterior parietal area and several frontal areas specific to this Allo‐to‐Ego conversion process. This finding has implications for understanding neuropsychological deficits that fall between strictly egocentric vs. allocentric.